Proposição de um índice de qualidade da água bruta afluente a estações convencionais de tratamento de água - Maria Eugenia Tavares Abreu de Souza (2008)
The proposition of a raw water quality index applying to conventional water treatment plants (RWQI) will allow evaluating the efficiency of the plant, not only concerning the water quality for public supply according to drinking water standard. Consequently, the natural water thatpresents high values of RWQI and WTPQI could not have the same efficiency of waters with low RWQI, meaning waters with lower quality with the same WTPQI value. The main objective of the proposition is to show the utility of this rate as a tool for systems of operation and production of potable water and for public information of the water quality as well. Thisresearch was made according the Delphi methodology, with help of specialists in the definition of weights and in the choice of quality parameters for the raw water to be used in theproposition of this index. Two questionnaires was sent to specialists. The first had the answersof weight and parameters, and the second had the feedback of the answers of the first one. Then the parameters scoring was structured, after the most relevant weights and parameters were determined according with the specialists opinion. This scoring was structured considering the impact occasioned in water treatment by the variation in parameters concentration. The optimum values of a parameter must have higher values in the parameter scoring, as low values must have lower values. The parameters scoring were determined after consultingbibliography, legislation and inquiring operators and researchers about the process of water supply potabilization. The last stage of this work was a mathematic formulation of the productory and somatory for aggregation of all variables to propose the RWQI and utilization of the rate in a conventional water treatment station. The productory was used to verify the influence of lower scoring parameters in rate values. The (RWQI) is an important information tool for the quality water sources like common stage that evaluates the performance from water treatment plants.